2015
DOI: 10.1042/bj20140450
|View full text |Cite
|
Sign up to set email alerts
|

Calcium/Ask1/MKK7/JNK2/c-Src signalling cascade mediates disruption of intestinal epithelial tight junctions by dextran sulfate sodium

Abstract: Disruption of intestinal epithelial tight junctions is an important event in the pathogenesis of ulcerative colitis. Dextran sodium sulfate (DSS) induces colitis in mice with the symptoms similar to ulcerative colitis. However, the mechanism of DSS-induced colitis is unknown. We investigated the mechanism of DSS-induced disruption of intestinal epithelial tight junctions and barrier dysfunction in Caco-2 cell monolayers in vitro and mouse colon in vivo. DSS treatment resulted in disruption of tight junctions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(92 citation statements)
references
References 40 publications
4
88
0
Order By: Relevance
“…Some have reported that TNFa-induced activation of NFkB and subsequent upregulation of MLCK triggers cytoskeletal activation, disruption of tight junctions, and enhanced permeability (Ma et al, 2005;Ye et al, 2006;Al-Sadi et al, 2016). Others have reported that ZO-1 relocalization can be driven by the activation of JNK1/2 signaling (Samak et al, 2014(Samak et al, , 2015Zhang et al, 2015). Interestingly, activation of the PXR has been reported to interact with both of these pathways (Zhou et al, 2006;Wang et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Some have reported that TNFa-induced activation of NFkB and subsequent upregulation of MLCK triggers cytoskeletal activation, disruption of tight junctions, and enhanced permeability (Ma et al, 2005;Ye et al, 2006;Al-Sadi et al, 2016). Others have reported that ZO-1 relocalization can be driven by the activation of JNK1/2 signaling (Samak et al, 2014(Samak et al, , 2015Zhang et al, 2015). Interestingly, activation of the PXR has been reported to interact with both of these pathways (Zhou et al, 2006;Wang et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…A significant body of evidence indicates that the disruption of intestinal epithelial TJ and elevated gut permeability to macromolecules play crucial role in the pathogenesis of many gastrointestinal diseases [12-15]. Recent studies demonstrated that different types of cellular stress affect the integrity of intestinal epithelial TJ and induce barrier dysfunction [16-19]. Evidence also suggests that acute bio-behavioral stress may affect the TJ in mouse intestinal epithelium in vivo [5-8].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies suggested that cell signaling involving intracellular calcium [Ca 2+ ] i ), c-jun N-terminal kinase-2 (JNK2) and c-Src may be involved in TJ disruption by osmotic stress [18, 19], dextran sulfate sodium (DSS) [16] and cyclic stretch in the intestinal epithelium [17]. [Ca 2+ ] i mediates stress-induced activation of JNK2 and c-Src, but the link between these signaling elements is unknown, as neither JNK2 nor c-Src are unknown to be activated directly by Ca 2+ .…”
Section: Introductionmentioning
confidence: 99%
“…Cells were seeded in 6-well plates and transfected at 60-70% confluence with miR-135a mimic or the mimic NC using Lipofectamine 2000 (Invitrogen, Carlsbad, CA, USA) according to the manufacturer's instructions [30]. After transfection for 48 h, the transfected cells were treatment with 2% DSS or S3I-201 for 4 days for further assays.…”
Section: Transfection Of Mirnamentioning
confidence: 99%
“…Cells maintained at 37°C in a humidified chamber of 5% CO 2 [29,30]. 100 μM S3I-201, an inhibitor of STAT3, was purchased from Calbiochem (La Jolla, CA, USA) and incubated for 1 h prior to DSS treatment [31].…”
Section: Cell Lines and Cell Culturementioning
confidence: 99%